Reconfigurable logic architecture, tools, and applications - Gaillardon, Pierre-Emmanuel (CRC Press, 2016)
During the last three decades, reconfigurable logic has been growing steadily and can now be found in many different fields. Field programmable gate arrays (FPGAs) are one of the most famous architecture families of reconfigurable devices. FPGAs can be seen as arrays of logic units that can be reconfigured to realize any digital systems. Their high versatility has enabled designers to drastically reduce time to market, and made FPGAs suitable for prototyping or small production series in many branches of industrial products. In addition, and thanks to innovations at the architecture level, FPGAs are now conquering segments of mass markets such as mobile communications. Reconfigurable Logic: Architecture, Tools, and Applications offers a snapshot of the state of the art of reconfigurable logic systems. Covering a broad range of architectures, tools, and applications, this book: Explores classical FPGA architectures and their supporting tools Evaluates recent proposals related to FPGA architectures, including the use of network-on-chips (NoCs) Examines reconfigurable processors that merge concepts borrowed from the reconfigurable domain into processor design Exploits FPGAs for high-performance systems, efficient error correction codes, and high-bandwidth network routers with built-in security Expounds on emerging technologies to enhance FPGA architectures, improve routing structures, and create non-volatile configuration flip-flops Reconfigurable Logic: Architecture, Tools, and Applications reviews current trends in reconfigurable platforms, providing valuable insight into the future potential of reconfigurable systems.
Includes bibliographical references (pages 477-479). - Print version record
Keywords: Adaptive computing systems; Field programmable gate arrays; Systèmes adaptatifs (Informatique); Réseaux logiques programmables par l'utilisateur; TECHNOLOGY & ENGINEERING; Mechanical